SOIL IMPROVEMENT IN SANDY SOILS AGAINTS LIQUEFACTION POTENTIAL DUE TO PALU EARTHQUAKE USING STONE COLUMN - Farkhantiansyah, Aggie
Liquefaction is natural phenomena which can be occur during earthquake. Indonesia is a county with high potential earthquake and in some region have big liquefaction potential by reason of the site have sandy soil and high ground water level. In 2018, earthquake and liquefaction has occurred in Palu. Many causalities and many lost that build concern regarding liquefaction potential. Now days, liquefaction potential can be reduced by installing stone column. Liquefaction analysis was carried out by using NCEER 1996 method with earthquake data from Palu 2018. For analysis purposes, SPT and CPT from field investigation in area of study data was used for basic analysis. The liquefaction would be developed based on SPT data at 17.65 m depth and based on CPT data 17.65 m depth. For reducing liquefaction potential, stone column would be installed. The stone column design was based on design chart from (Bouckovalas, et al., 2009) by reason of this design chart had been corrected in term of pore water pressure generation equation that made this design chart more accurate. The configuration of stone column has design 1 m of diameter, 1.7 m spacing for triangular pattern and 1.5 m spacing for rectangular pattern. As is stone column installed, when re-analyzed liquefaction potential with NCEER method, SPT number will be corrected due to installation of stone column. CRR will be corrected. CSR will be corrected due to differential of stiffness. When stone column is installed, the factor of safety will be increased.